Adelaide Ristori cantante - Mingozzi, Davide (Drammaturgia, 2024)
For a long time, studies on Adelaide Ristori have been interested in her life, her success and her importance for the Italian theater. On the other hand, the musical interests of the noblewoman were less studied; however, music had a fundamental role in the life and career of the actress. We have little information on her musical training and interests. The donation of the actress’s archive to the Museo Biblioteca dell’Attore in Genoa has opened new fronts of studies in this regard. Among the material preserved in it, in addition to various letters and incidental music, there are some musical compositions dedicated to Ristori and performed by her. For example, some romances by Federico Ricci and Michele Novaro. This essay offers an overall look at Ristori as a musician, her education and her musical interests. Some compositions performed by her are also analysed, which are useful for understanding her vocality.